Altered hippocampal kynurenine pathway metabolism contributes to hyperexcitability in human mesial temporal lobe epilepsy–hippocampal sclerosis. (22nd June 2021) - Dey, Soumil; Banerjee Dixit, Aparna; Tripathi, Manjari; Doddamani, Ramesh Sharanappa; Sharma, Mehar Chand; Lalwani, Sanjeev; Chandra, Poodipedi Sarat; Banerjee, Jyotirmoy
Abstract : Background and Purpose: Glutamate receptor‐mediated enhanced excitatory neurotransmission is typically associated with mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE‐HS). Kynurenic acid and quinolinic acid are two important tryptophan–kynurenine pathway metabolites that modulate glutamate receptor activity. This study was designed to test the hypothesis that alteration in metabolism of tryptophan–kynurenine pathway metabolites in the hippocampus of patients with MTLE‐HS contributes to abnormal glutamatergic transmission. Experimental Approach: Levels of tryptophan–kynurenine pathway metabolites were determined using HPLC and LC–MS/MS in hippocampal samples from patients with MTLE‐HS, compared with autopsy and non‐seizure control samples. mRNA and protein expressions of tryptophan–kynurenine pathway enzymes were determined by qPCR and Western blot. Spontaneous glutamatergic activities were recorded from pyramidal neurons in the presence of kynurenine and kynurenic acid, using whole‐cell patch clamp. Key Results: Levels of kynurenic acid were reduced and quinolinic acid levels were raised in hippocampal samples from MTLE‐HS patients, whereas kynurenine levels remained unaltered, compared with levels in non‐seizure controls. Spontaneous glutamatergic activity in MTLE‐HS hippocampal samples was higher than that in non‐seizure controls. Treatment with kynurenine inhibited glutamatergic activity in non‐seizure control samples but not in MTLE‐HS samples. However, exogenously applied kynurenic acid inhibited glutamatergic activity in both non‐seizure control and MTLE‐HS hippocampal samples. Also, levels of kynurenine aminotransferase II and its cofactor pyridoxal phosphate were reduced in MTLE‐HS samples. Conclusion and Implications: Our findings indicate that altered metabolism of tryptophan–kynurenine pathway metabolites in hippocampus could contribute to hyperglutamatergic tone in patients with MTLE‐HS.